Dual-Band Microstrip Patch Antenna Miniaturization Using Metamaterial - Indrasen Singh; Vijay Shanker Tripathi; Sudarshan Tiwari (Journal of Engineering)
A dual-band microstrip patch antenna is designed and analyzed using metamaterial artificial substrate. Metamaterial based substrate is designed using Square Split Ring Resonator (SSRR) and Wire Strip. The antenna is tuned to work at two resonating frequencies in the frequency range from 1 GHz to 4 GHz depending on the geometric specifications of SSRR, strip line, radiating patch, and feed location point. Proposed antenna provides good return loss behavior at both resonating frequencies. The obtained VSWR at both resonating frequencies is very much near to 1. Proposed antenna covers applications in mobile communication and Wi-MAX. Proposed patch antenna is compared with the conventional patch antenna, which shows the significant miniaturization as compared to conventional patch antenna.